The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jcma.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between the Expanded Disability Status Scale and inflammatory markers in multiple sclerosis?

Abstract: According to this study, inflammation may have a role in the pathogenesis of MS and in patients with EDSS > 5. Additionally, NLR and CRP levels may be discriminative factors of adverse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 19 publications
4
38
1
Order By: Relevance
“…However, as mentioned earlier, in MS patients this correlation disappears and they tend to be inversely (but not significantly) associated. Prior studies find that EDSS value is strongly correlated with axonal damage and neurodegeneration [ 29 , 30 ]. Furthermore, a possible mechanism for MS progression and axonal loss could be via oxidative stress, caused by a decrease in antioxidant levels, which might lead to DNA damage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as mentioned earlier, in MS patients this correlation disappears and they tend to be inversely (but not significantly) associated. Prior studies find that EDSS value is strongly correlated with axonal damage and neurodegeneration [ 29 , 30 ]. Furthermore, a possible mechanism for MS progression and axonal loss could be via oxidative stress, caused by a decrease in antioxidant levels, which might lead to DNA damage [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited prior literature regarding the NLR in MS; Demirci and colleagues were the first to explore this area and found that an elevated NLR could discriminate MS from healthy controls, was related to neurological disability scores, and was further increased in flares compared to remission [20]. Several subsequent studies have confirmed similar findings [13, 20, 21], although one study could not replicate associations with disability scores [22]. None of these studies carefully examined the role of disease-modifying therapies however; nor did they look at MRI-related disease outcomes such as cerebral atrophy or quantified T2-hyperintense lesion volume.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, in this work it was revealed that, in patients with a higher concentration of homocysteine, there are increases in the concentration of tumor necrosis factor-alpha 1 receptor (TNF-α receptor 1) and ICAM. In the study by Guzel et al [ 50 ], it was shown that the concentration of homocysteine is statistically significantly higher in patients with an EDSS greater than 5. The data obtained confirm the association of hyperhomocysteinemia with the progression and severity of disability in patients with MS.…”
Section: The Role Of Homocysteine In Endothelial Dysfunction In Mumentioning
confidence: 99%